(3TQM eNJUQ CHj LYaQ GdWMGhis - (3CMeO Hf Ydj GdnqQGRj, CHh HcQ GdLUGU,J (B370 (3g` s; (3CMeO Hf eMeO Hf SdGeI Hf SdeI GdCROqj GdWMGhj, CHh LYaQ,J (B321 (3g` s
(3ChdgG (B:s
(3HGH GdeRGQYI s
(3BNQgG (B:s
(3BNQ GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdQGHYs
(3fSNI QGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdMfajs